Identification of Phytochemical Compounds and Antioxidant Activity in Methanol Extract of Basa Genep Seasoning - Ni Made Ayu Suardani Singapurwa; Putu Diah Wahyuni; I Putu Candra (PT FORMOSA CENDEKIA GLOBAL, 2023)
Basa genep is a basic spice in traditional Balinese cuisine used in making traditional food. The purpose of this study was to identify the densest type, content, and antioxidant activity of methanol extract of genep bases using an extraction method whose testing was carried out with a Uv-Vis spectrophotometer (Biochrom). The results found that base genep methanol extract had flavonoid levels of 1427.90±60.46 mg QE/100g, tannin levels of 3277.05±65.33 mg TAE/100g, total phenol levels of 2398.08±72.195 mg GAE/100g with IC50 values of 144.43±6.673 ppm including medium category